Implementation of Bloom's Theory in Quality Improvement Collaborative Strategies to Reduce Preeclampsia Cases - Syabrullah, Andreas; Mawarti, Herin; Masruroh, Masruroh; Zulfikar Asumta, Muhammad; Zulfikar Asumta, Muhammad (Jurnal Indonesia Sosial Sains, 2025)
The main target of the third goal of the Sustainable Development Goals (SDGs) regarding health and well-being is to reduce the Maternal Mortality Rate to below 70 per 100,000 live births by 2030. Preeclampsia is the leading cause of maternal death in 2023. Reducing the Maternal Mortality Rate will not be effective if it relies solely on government programs without support and participation from all parties. The Quality Improvement Collaborative is a form of cooperation among staff, professions, and work units focused on maximizing the use of resources to achieve the shared goal of improving patient care quality. This activity aims to deepen the understanding of the Quality Improvement Collaborative in reducing preeclampsia cases, using a socialization method involving several work units. The community service on Quality Improvement Collaborative to reduce preeclampsia cases was held on January 17, 2025, in two sessions. It used the Participatory Learning and Action (PLA) approach and included three stages: preparation, implementation, and evaluation. The evaluation results of the pre-test and post-test using the Wilcoxon test showed a significant increase in knowledge, with a p-value of 0.000. This service effectively increased knowledge, which serves as the main foundation for taking action. Similar activities can be continued by utilizing more innovative media to enhance their effectiveness.